Characterization, Knockdown and Parental Effect of Hexokinase Gene of Cnaphalocrocis medinalis (Lepidoptera: Pyralidae) Revealed by RNA Interference - Shakeel, Muhammad (Genes (Basel), 2020)
Hexokinase (HK) is a key enzyme in chitin biosynthesis in insects and plays an important role in development and energy regulation. It also performs a crucial role in the synthesis of Glucose-6-phosphate and its putative functions are studied via injection of dsRNA corresponding to the hexokinase gene from Cnaphalocrocis medinalis (CmHK). This study was designed to analyze the characteristics and expression patterns of HK-related genes in various tissues of C. medinalis at different developmental stages. The CmHK ORF is a 1359 bp in length, encoding a protein of 452 amino acids, with homology and cluster analysis showing that CmHK shares an 85.11% sequence similarity with hexokinase from Ostrinia furnacalis. CmHK was highly expressed in the ovary and in the fifth instar larvae. Injection of dsCmHK significantly suppressed mRNA expression (73.6%) 120 h post-dsRNA injection as compared to a control group. The results demonstrated an increased incidence of larval and pupal mortality of 80% and 78%, respectively, with significant variation in the sex ratio between males (68.33%) and females (35%), overt larval deformities, and a reduction in average weight gain observed 120 h post-dsRNA injection. In addition, dsCmHK-injected C. medinalis showed a significant reduction in ovulation per female and larval hatching rate, along with increased larval and pupal mortality and variation in male and female emergence over three generations (G1, G2, and G3). Taken together, the outcomes of the study provide a foundation to study gene function and a new dimension to control C. medinalis by transgenic RNAi technology.